Pitch‐Angle Scattering of Inner Magnetospheric Electrons Caused by ECH Waves Obtained With the Arase Satellite. Issue 23 (24th November 2020) - Fukizawa, M.; Sakanoi, T.; Miyoshi, Y.; Kazama, Y.; Katoh, Y.; Kasahara, Y.; Matsuda, S.; Matsuoka, A.; Kurita, S.; Shoji, M.; Teramoto, M.; Imajo, S.; et al.
Abstract: Electrostatic electron cyclotron harmonic (ECH) waves are generally excited in the magnetic equator region, in the sector from nightside to dayside during geomagnetically active conditions, and cause the pitch angle scattering by cyclotron resonance. The scattered electrons precipitate into the Earth's atmosphere and cause auroral emission. However, there is no observational evidence that ECH waves actually scatter electrons into the loss cone in the magnetosphere. In this study, from simultaneous wave and particle observation data obtained by the Arase satellite equipped with a high‐pitch angular resolution electron analyzer, we present evidence that the ECH wave intensity near the magnetic equator is correlated with an electron flux inside the loss cone with an energy of about 5 keV. The simulation suggests that this electron flux contributes to the auroral emission at 557.7 nm with an intensity of about 200 R. Plain Language Summary: Wave‐particle interaction via electrostatic electron cyclotron harmonic (ECH) waves is a promising generation mechanism for precipitating electrons into Earth's atmosphere and producing diffuse auroras. However, there is no observational evidence that ECH waves scatter electrons to cause auroral emissions. In this study, based on observation data obtained by the Arase satellite equipped with a high‐angular resolution electron analyzer, we identified an event during which the ECH wave intensity near the magnetic equator was correlated with the electron flux that precipitated into the Earth's atmosphere. Our simulation suggests that this electron flux contributes to visible oxygen green‐line auroral emission. Key Points: We found an event that electron cyclotron harmonic wave intensity correlated with electron flux in a loss cone with ~5 keV energy The pitch‐angle diffusion coefficient of 5 keV is larger than those of other energies when the electron temperature is 8 eV and the wave normal angle is 88.5° The electron flux correlated with the ECH wave intensity can cause 557.7 nm auroral emission with ~200 R intensity